2016
DOI: 10.1016/j.jcm.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Spasticity in Patients With Cerebral Palsy After Spinal Manipulation: Case Series

Abstract: Objective: The purpose of this case series was to report quantitative changes in wrist muscle spasticity in children with cerebral palsy after 1 spinal manipulation (SM) and a 2-week course of treatment. Methods: Twenty-nine patients, aged 7 to 18 years, with spastic forms of cerebral palsy and without fixed contracture of the wrist, were evaluated before initiation of treatment, after 1 SM, and at the end of a 2-week course of treatment. Along with daily SM, the program included physical therapy, massage, ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…6,7,8,9,11,12 Previous studies conducted on stroke patients and CP children provided only descriptive information about such influence. 13,14,15 Muscle spasticity was the primary outcome measure of the study. It was measured quantitatively with a Neuro-Flexor device, a valid and reliable tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,8,9,11,12 Previous studies conducted on stroke patients and CP children provided only descriptive information about such influence. 13,14,15 Muscle spasticity was the primary outcome measure of the study. It was measured quantitatively with a Neuro-Flexor device, a valid and reliable tool.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated based on data from the preliminary research on the influence of SM on muscle spasticity, 15 with confidence level of 95% and power of 80%. Aimed at detecting the size effect of 1.92 newton in the mild spasticity group, with an SD of 2.92, the estimated sample size was calculated to be at least 37 participants in each group.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint mobilization provides a well-suited intervention for ankle rehabilitation, but the effectiveness of a randomized control trial study in children with CP has not been confirmed. As part of manual therapy, there are spine manipulation studies for cerebral palsy [ 26 , 27 ]. Manipulation is a high-velocity (thrust) technique, while joint mobilization is a relatively safe technique with low-velocity techniques [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the child grows, the progressive shortening of the calf muscles secondary to spasticity develop to such a significant degree that the contracture may require surgical lengthening of the muscle but since children's feet are relatively flexible and adaptable, The treatment program for a child with HCP may include different options: Exercises, bracing, casting, oral medications and orthopedic surgery. Because of the limited efficiency of "traditional" treatments as exercises and bracing, a wide range of complementary and alternative therapies are used for muscle tone and Range of Motion (ROM) management [6,7] . Serial casting is the use of a series of progressive muscle stretching casts to increase muscle length using prolonged low load stress to contracted tissue [8] .…”
Section: Introductionmentioning
confidence: 99%